1998
DOI: 10.1590/s0100-879x1998000100023
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-12 and protective immunity to schistosomes

Abstract: The attenuated vaccine against Schistosoma mansoni induces Th1-mediated protective immunity and we have sought to identify a role for IL-12 in this model. Elevated levels of IL-12 (p40 mRNA) were detected in the lymph nodes (LN) and the lungs of vaccinated mice, whilst treatment of vaccinated mice with anti-IL-12 antibodies decreased the ratio of IFNγ:IL-4 secreted by in vitro-cultured LN cells. However, there was only marginal abrogation of the level of resistance in these mice. Soluble antigens from the lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…1998). We speculate that antigenic molecules from lung‐stage parasites have a propensity to stimulate accessory cells to produce IL‐12 and thus favour the polarised development of Th1 cells (Mountford et al . 1997).…”
Section: Introductionmentioning
confidence: 99%
“…1998). We speculate that antigenic molecules from lung‐stage parasites have a propensity to stimulate accessory cells to produce IL‐12 and thus favour the polarised development of Th1 cells (Mountford et al . 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the specific type of protective immune response generated by these antigens is frequently discordant between animal and human studies. Th1-type vaccine responses are frequently protective in murine models (33)(34)(35)46), while Th2-type responses are associated with resistance to reinfection in humans (19,32,39). This divergence makes generalizability from animal models of resistance problematic and underscores the importance of well-controlled, immunoepidemiology studies of schistosomiasis in humans.…”
mentioning
confidence: 99%
“…In mansonian schistosomiasis, hepatic fibrosis is initiated by vigorous granulomatous responses to tissueentrapped parasite eggs that is mainly orchestrated by cross-regulatory CD4 + T cell. Although an appropriate 1 response to S. mansoni larvae is associated with high protection levels [17] and 2 response to soluble egg antigens is known to promote excessive fibrotic organ damage [18], there are actually no good or bad T cell responses to Schistosoma larvae or eggs. Earlier studies in experimental schistosomiasis have shown the essential role for CD4 + T cells in granuloma formation and disease [19].…”
Section: Discussionmentioning
confidence: 99%